Відповідь:
1. 1) =4
2) =-13
3)
2. х+17=13
х=13-17
х=-4
-4+17=13
-26-х=-16
-х=-16+26
-х=10
х=-10
-26-(-10)=-16
3. а) 0,166666666
4. Якщо рахувати 0, то 13 цифр
сума = -26
-8+(-7)+(-6)+(-5)+(-4)+(-3)+(-2)+(-1)+0+1+2+3+4=-26
Відповідь:
1. 1) =4
2) =-13
3)![\frac{19*6-23*4+19*3}{36} =\frac{114-92+57}{36} =\frac{79}{36} =2\frac{7}{36}](/tpl/images/1540/6421/3fe83.png)
2. х+17=13
х=13-17
х=-4
-4+17=13
-26-х=-16
-х=-16+26
-х=10
х=-10
-26-(-10)=-16
3. а) 0,166666666
4. Якщо рахувати 0, то 13 цифр
сума = -26
-8+(-7)+(-6)+(-5)+(-4)+(-3)+(-2)+(-1)+0+1+2+3+4=-26